Industrial park comprehensive demand response scheduling method based on multi-energy cooperation - LI SHIYING; WANG LI; HU FAN; XIONG WEN; ZENG SHUNQI; AI QIAN; YU ZHIWEN; LIAO JIANPING; JIANG ZIQING (2020)
The invention discloses an industrial park comprehensive demand response scheduling method based on multi-energy cooperation. The method comprises steps that an operator executes day-ahead load prediction and reports the day-ahead load prediction to ISO or bids to the power market; the operator obtains a load reduction index from the ISO or the market clearing result; the operator determines a scheduling plan by solving a comprehensive demand response optimization model and informs a consumer and the CCHP of the result; if any consumer or CCHP cannot respond according to an instruction, the operator rearranges the scheduling plan, otherwise, the response is executed; on the second day, the consumer adjusts the load demand, reduces the power load or increases the heat and cold loads at theappointed time, and the CCHP correspondingly adjusts the yield to balance the load. The method is advantaged in that various interactive modes such as interruptible load, multi-energy demand coupling,multi-energy supply and d